THE ROLE OF BINARY METAPHORICAL OPPOSITIONS IN A POETIC TEXT - Kamienieva, Iryna (SWorld-Ger Conference proceedings, 2023)
The article is devoted to the study of the universal binary oppositions which are part of the primary classifications, forming the basis of any mythological picture of the world. It has been also considered metaphorical binary oppositions in literature an